Molecular docking analysis of acetogenin and procyanidin, components of soursop (Annona muricata Linn.) seed, as potential anti-cervical cancer agents - Pravita, Nabila Cahya; Fazilla, Rizki Fakhri; Febrian, Tobi; Mellina, Echa Dian; Kumara, Gusti Made Bagus; Nugraha, Muhammad Aditya; Vernanda, Pramyudha; Auli, Winni Nur; Saputro, Anjar Hermadi (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2023)
Cervical cancer is one of the most prevalent cancers among women. This study aimed to investigate the molecular interactions of acetogenin and procyanidin, compounds found in soursop (Annona muricata Linn.) seed extract, as potential anti-cervical cancer agents using a molecular docking approach. The software tools used included Biovia Discovery Studio® 2024, Autodock Tools 1.5.6, Avogadro, pkCSM, PubChem, Notepad++, and Molview. Molecular docking analysis focused on the interaction of these compounds with the human vaccinia-related kinase 2 (VRK-2) protein (PDB ID: 5UU1). The native ligand-5UU1 protein complex exhibited two hydrogen bonds, a binding free energy of -8.84 kcal/mol, and an inhibition constant of 331.88 nM. In comparison, acetogenin formed three hydrogen bonds with 5UU1, achieving a binding free energy of -7.33 kcal/mol and an inhibition constant of 4.21 nM. Similarly, procyanidin also formed three hydrogen bonds, with a binding free energy of -2.99 kcal/mol and an inhibition constant of 6.38 nM. The results indicate that both acetogenin and procyanidin have potential as anti-cervical cancer agents, with acetogenin demonstrating stronger binding affinity and inhibition potential compared to procyanidin.